Competitive and collaborative relationship between Al–3P and TiB2 nanoparticles in the microstructure manipulation of eutectic Al–Si alloys - Yi-Lu Li; Bai-Xin Dong; Hong-Yu Yang; Dan Luo; Shi-Li Shu; Zhi-Fa Wang; Jie Kang; Jia Meng; Chang-Jie Luo; Cheng-Gang Wang; Kuang Cao; Jian Qiao; et al. (Journal of Materials Research and Technology)
In this work, the synergistic effects of the modifier Al–3P master alloy and nano-TiB2 ceramic particles on the microstructure and mechanical performance of cast eutectic Al–Si alloys were investigated. Results showed that AlP and nano-TiB2 particles served as efficient heterogeneous nucleation sites of Si and α-Al, respectively. Incorporated TiB2 and Al–3P performed the best manipulating potency on the solidification microstructure of Al–Si alloys than separately added, primary Si was significantly refined and the transition of Al–Si eutectic was promoted. Room-temperature and high-temperature tensile strength were also markedly enhanced, the yield strength, ultimate tensile strength and fracture strain of eutectic Al–Si alloys manipulated by Al–3P + nano-TiB2 particles were increased by 36.4%, 31.7% and 32.1% at 250 °C and 60.0%, 42.0% and 50.9% at 300 °C, respectively, in comparison to the unmodified alloys. The enhanced high-temperature strength was attributed to the refinement of primary Si and α-Al, which was achieved through the synergistic effects of nano-TiB2 particles and Al–3P. Then the grain boundary density increased, with finer eutectic Si and nanoparticles being effectively pinned at the grain boundaries, thereby boosting the mechanical performance. This study provides theoretical research and experimental basis for the development and application of heat-resistant aluminum alloys.